Resilience and Adaptation: Urban Muslim Communities in DKI Jakarta Facing Environmental Challenges - Luhuringbudi, Teguh; Abdiguno , Panggih (Al-madinah: Journal of Islamic Civilization, 2024)
This study examined the ways in which Muslim communities in DKI Jakarta have adapted and demonstrated resilience in the context of environmental challenges. This study focuses on the adaptation strategies developed by Muslim communities in response to environmental disturbances, including flooding, pollution, and water quality degradation. To investigate these strategies, the study employs theoretical approaches drawn from the fields of socio-ecological resilience, climate justice, and urban green infrastructure. The research methods employed included a qualitative analysis of environmental policies, community practices, and adaptive responses. The findings indicated that the resilience of these communities was underpinned by robust religious values, social cohesion, and pioneering adaptation strategies. The implementation of urban green infrastructure has been demonstrated to enhance the adaptive capacity of communities in response to climate change. Furthermore, this study underscored the necessity for the equitable distribution of environmental benefits in order to safeguard vulnerable communities. One limitation of this study was that its analysis was predominantly qualitative and focused on Muslim communities in DKI Jakarta. The findings of this study made a significant scientific contribution by demonstrating that a holistic approach that integrated social, cultural, and ecological aspects could effectively enhance community resilience to climate change. Additional research is required to test this hypothesis in diverse contexts with a more comprehensive quantitative approach.